Case study on the running of advanced topics in macroeconomics I - Madeira, J. (Exemplos de práticas pedagógicas e estratégias de inovação pedagógica no Iscte, 2023)
This is a case study on the running of Advanced Topics in Macroeconomics I, a course unit of the PhD in Economics and PhD in Finance at Iscte, during the academic year of 2022/2023 (the only year in which I taught the unit so far). The teaching content in macroeconomics in economic degrees is usually highly theoretical (Xu et al., 2023). This is at odds with modern macroeconomic research which uses a wide variety of empirical methods (Chari and Kehoe, 2007). To address the criticism and reflect the practice in modern research, I adjusted the content of macroeconomics teaching at Iscte to incorporate a higher content of data analysis. I also introduced the teaching of programming using Stata and Matlab. These software packages are used in other courses units of the PhD in Economics and PhD in Finance at Iscte but including them in the teaching of macroeconomics aids their learning of the software and enables students to become familiar with the most common applications used in macroeconomics research. Making these changes to the course unit was simple and easy (Iscte allows teachers great freedom in adjusting the content of course units without significant bureaucracy involved). Students’ satisfaction with the teaching at the end of the term was high.